GH25 lysozyme mediates tripartite interkingdom interactions and microbial competition on the plant leaf surface - Zarah Sorger; Priyamedha Sengupta; Klara Beier-Heuchert; Jaqueline Bautor; Jane E. Parker; Eric Kemen; Gunther Doehlemann (Proceedings of the National Academy of Sciences, 2025)
Microbial communities inhabiting plants have emerged as crucial factors in regulating plant health and defense against disease-causing pathogens. The yeast Moesziomyces bullatus ex. Albugo (MbA) on Arabidopsis produces a glycoside hydrolase 25 (GH25) protein that regulates the leaf microbiome by antagonizing the pathogenic oomycete Albugo laibachii . Applying MbA or GH25 rescued Arabidopsis thaliana shoot fresh weight under A. laibachii infection, highlighting their crop protection potential. Interaction assays revealed no antagonistic activity of GH25 against other plant pathogenic oomycetes or fungi besides A. laibachii . We identified a community of bacteria closely associated with A. laibachii. Three of these bacteria are inhibited by GH25 and one of them, Curtobacterium sp. could override the inhibition of A. laibachii by MbA . This points to a tripartite antagonism where Curtobacterium and A. laibachii protect each other from MbA . Moreover, Curtobacterium selectively inhibits other A. laibachii -associated bacteria not targeted by MbA but that themselves suppress A. laibachii . This study uncovers an interkingdom network where GH25 lysozyme shapes microbial interactions between yeast, oomycete, and associated bacteria.